2016
DOI: 10.1007/s11084-016-9516-z
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Polymerization on Oxide Minerals

Abstract: It has long been suggested that mineral surfaces played an important role in peptide bond formation on the primitive Earth. However, it remains unclear which mineral species was key to the prebiotic processes. This is because great discrepancies exist among the reported catalytic efficiencies of minerals for amino acid polymerizations, owing to mutually different experimental conditions. This study examined polymerization of glycine (Gly) on nine oxide minerals (amorphous silica, quartz, α-alumina and γ-alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 63 publications
1
44
0
Order By: Relevance
“…The interaction between silica and molecular components of peptide‐ and depsipeptide‐forming heterogeneous systems have been documented . Reactive hydroxy groups and Lewis acid and base terminations are expected to occur on other metal oxide surfaces and interact with HAs .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between silica and molecular components of peptide‐ and depsipeptide‐forming heterogeneous systems have been documented . Reactive hydroxy groups and Lewis acid and base terminations are expected to occur on other metal oxide surfaces and interact with HAs .…”
Section: Figurementioning
confidence: 99%
“…Earlier work has also suggested that organic acids esterified with surface hydroxyl groups are potentially important for mineral‐catalyzed amide bond formation under prebiotic conditions . Although silicates were present on early earth, and SiO 2 is a primary component of basalt and primary magmatic rock, silica has been thought to be of minor importance in the prebiotic formation of oligopeptides due to limited reactivity of the surface upon exposure to liquid‐phase solutions containing AAs . However, the interaction with coadsorbates or coreactants, such as esterified surface hydroxy groups, was not considered.…”
Section: Figurementioning
confidence: 99%
“…A systematic study of the polymerization of glycine on mineral surfaces showed the order of catalytic efficiency: rutile > anatase > γ-alumina > forsterite > α-alumina > magnetite > hematite > quartz > amorphous silica. 98 Martra and coworkers prepared poly-Gly up to 16 units long by condensation of the amino acid vapour (130 °C) on TiO 2 (anatase) and amorphous SiO 2 surfaces. 99 That line of research 100 opens a number of possibilities for prebiotic synthesis, but it has to be taken into consideration that there is a quite significant difference in polymerization efficiency for different amino acids on different minerals, e.g.…”
Section: +mentioning
confidence: 99%
“…16 Given that the amino acid molecules exhibit two functional groups with nitrogen and oxygen atoms capable of acting as electron-pair donors, they can be considered as suitable ligands for vacant-orbital transition metal ions. In particular, the reactions of complexation of Cr(III) by amino acids might be related to the problem of the origin of the first peptides on prebiotic Earth, 17 since transition metal ions have been shown to catalyze the formation of peptide bonds between the amino acid monomers acting as ligands. 18 The substitution reactions on aqua, [19][20][21][22][23][24][25][26] hydroxo, 27 and ammonia 28 complexes of Cr(III) by amino acids have been the subject of several kinetic studies.…”
Section: Introductionmentioning
confidence: 99%